Application of Integrative Approach in the System of Engineering Education by the Example of Studying of Linear Algebra - Kolomiyets, Aliona (Pedagogical Discourse, 2014)
The essence of the concepts integration, integrative approach has been revealed in the article; the attention is accented on expedience and importance of including of integrative approach into the educational process of higher school. It is found out that the process of integration can have a few levels, in particular: integrated educational courses, integrated special courses, integrated lessons; integrative approach is optimal today for engineering education as for conducting the lessons. The introduction of the described approach into the educational process has been offered in the article by the example, namely, the fragment of integrated lesson of higher mathematics and physics has been shown, the topic of the lesson is «Determinants. Matrices. Systems of lineal equations». By the example of the designed mathematical tasks the introduction of integrative approach at high school has been shown. The importance of the studied principle for forming motivation of educational-cognitive activity of the future engineers has been mentioned.